2020
DOI: 10.1155/2020/2950536
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of Antenatal Depression and Associated Factors among Pregnant Women in West Badewacho Woreda, Hadiyya Zone, South Ethiopia: Community Based Cross Sectional Study

Abstract: Background. Antenatal depression is prevalent and serious problems that is associated with psychosocial factors, obstetric history, and history of psychiatric illness. Evidence on prevalence and factors associated with antenatal depression at community level is limited in Ethiopia. The aim of this study was assessing the prevalence of antenatal depression and associated factors among pregnant women in West Badewacho Woreda, Hadiyya Zone, South Ethiopia, 2018. Methods. A community based cross sectional study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
3
6
2
Order By: Relevance
“…The current study also found that pregnant women with a previous history of obstetric complications were three times more likely to have AD compared to those without a history of past obstetric complications. This finding was in agreement with the previous reports, 22 , 43 which indicated that previous and current obstetric complications significantly increase the likelihood of development of AD amongst pregnant women. The experience of a previous obstetric complication is known to increase the likelihood of recurrence, a fact that is emphasised to women at the time of debriefing them to encourage them to seek care early to mitigate the recurrence and their consequences.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The current study also found that pregnant women with a previous history of obstetric complications were three times more likely to have AD compared to those without a history of past obstetric complications. This finding was in agreement with the previous reports, 22 , 43 which indicated that previous and current obstetric complications significantly increase the likelihood of development of AD amongst pregnant women. The experience of a previous obstetric complication is known to increase the likelihood of recurrence, a fact that is emphasised to women at the time of debriefing them to encourage them to seek care early to mitigate the recurrence and their consequences.…”
Section: Discussionsupporting
confidence: 94%
“…This was consistent with previous studies such as from North Ethiopia (31.1%), 18 Adama, Ethiopia (31.2%), 19 Bangladesh 20 and Nairobi, Kenya (32.9%). 21 but higher than the findings from South Ethiopia (23.3%), 22 Vietnam (25%), 23 South Ethiopia (16.3%) 24 and North West Ethiopia (15.2). 25 However, higher findings of up to 80% have been reported from Pakistan.…”
Section: Discussioncontrasting
confidence: 55%
“…Figure 2 shows the distribution of articles from Ethiophia, Kenya, Tanzania, Qatar, Nigeria, Thailand, Rwanda, and China. 0.81 0.37 1.81 (Duko et al, 2019) 2.14 1.49 3.11 (Keliyo et al, 2021) 3.34 1.50 7.43 (Lodebo et al, 2020) 5.78 2.36 14.13 (Manongi et al, 2020) 2.25 1.26 4.02 (Massae et al, 2021) 0.61 0.37 0.98 (Naja et al, 2021) 3.20 1.70 5.90 (Oboro et al, 2022) 4.70 2.99 7.38 (Umuziga et al, 2022) 4.45 1.83 10.84 (Yu et al, 2020) 2.37 1.20 4.66 (Zelalem et al, 2020) 2.07 1.12 3.87 (Zeng et al, 2015) 0.92 0.88 0.97 . The Forest plot indicates the effect of marital status on the incidence of antenatal depression.…”
Section: Resultsmentioning
confidence: 99%
“…It is a multifaceted illness that has varying consequences for a woman's mental health, physical health, the family's functioning, and her children's [ 11 – 13 ]. Antenatal depressive symptoms have the potential to impact negatively upon health service utilization and thereby contribute to increased perinatal complications, adverse pregnancy outcomes, and maternal mortality [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%